The Relationship Between Knowledge and Attitudes of Pregnant Women by Preventing the Transmission of HIV/AIDS from Mother to Child - Fathia Fakhri Inayati Said; Nasrianti Nasrianti; Fenska Narly Makualaina; Hasnia Hasnia (Indonesian Journal of Global Health Research, 2024)
Human Immunodeficiency Virus (HIV) is an infection that attacks the body's immune system, more specifically white blood cells called Cluster of Differentiation 4 (CD4) cells. World Health Organization (WHO) data Based on SIHA Ministry of Health data, HIV cases up to March 2022 totaled 466,978 cases. Papua itself is in 5th position after DKI Jakarta 76,103, East Java 71,909, West Java 52,970, Central Java 44,649 and Papua 41,286. Meanwhile, for cases of AIDS sufferers, Papua has the highest number of cases, namely 137,397 people (Ministry of Health of the Republic of Indonesia, 2020) Research Objectives: To determine the Relationship between Knowledge and Attitudes of Pregnant Women with HIV/AIDS Prevention at the Harapan Health Center. Research Methods: The type of research used is quantitative research using correlation studies. Sampling technique Total sampling of 38 respondents. Results: Data analysis with Multiple Regression test found that there is a relationship between Knowledge and Attitude with the prevention of HIV/AIDS transmission from mother to child unit. Conclusion: There is a Significant Relationship between Knowledge and Attitude and Prevention of HIV/AIDS Transmission from Mother to Child.